2022
DOI: 10.3389/fviro.2022.849936
|View full text |Cite
|
Sign up to set email alerts
|

Alpha, Beta, Delta, Omicron, and SARS-CoV-2 Breakthrough Cases: Defining Immunological Mechanisms for Vaccine Waning and Vaccine-Variant Mismatch

Abstract: The COVID-19 pandemic, caused by the SARS-CoV-2 coronavirus, is responsible for over 400 million cases and over 5. 5 million deaths worldwide. In response to widespread SARS-CoV-2 infection, immunization of the global population has approached 60% one dose and 54% full dose vaccination status. Emerging data indicates decreasing circulating antibody levels as well as decreases in other immune correlates in vaccinated individuals. Complicating the determination of vaccine effectiveness is the concomitant emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
(60 reference statements)
0
20
0
Order By: Relevance
“…These mechanical regulations during viral invasion were further validated by the more infectious D614G mutation of SARS2-S. D614G mutation, located outside of the RBD of the S1 subunit, causes more fatality and is inherited in Alpha, Beta, Delta and recent Omincron SARS-CoV-2 virus 82 , 83 , 84 , 85 , 86 , 87 , 88 . A recent study showed that D614G converts the S1 protein conformation (RBD and N-terminal domains of S1 subunit) to an ACE2-binding fusion-competent state and thus may increase viral infectivity [89] .…”
Section: Mechanical Force In Virus Invasionmentioning
confidence: 87%
“…These mechanical regulations during viral invasion were further validated by the more infectious D614G mutation of SARS2-S. D614G mutation, located outside of the RBD of the S1 subunit, causes more fatality and is inherited in Alpha, Beta, Delta and recent Omincron SARS-CoV-2 virus 82 , 83 , 84 , 85 , 86 , 87 , 88 . A recent study showed that D614G converts the S1 protein conformation (RBD and N-terminal domains of S1 subunit) to an ACE2-binding fusion-competent state and thus may increase viral infectivity [89] .…”
Section: Mechanical Force In Virus Invasionmentioning
confidence: 87%
“…A study of breakthrough infections caused by the Delta variant of SARS-CoV-2 showed similar peak viral loads between vaccinated and unvaccinated subjects ( 40 ). Specimens collected from vaccinated individuals with breakthrough infections can have late CT values, with both Delta and Omicron variants ( 41 43 ).…”
Section: Interpretation Considerationsmentioning
confidence: 99%
“…Potential solutions to vaccine waning include (but are not limited to): i) further investigation into second generation, multivalent vaccines, ii) the humoral IgA mucosal response, and iii) development beyond S-targeting vaccines towards broad stimulation and priming of adaptive T-and B-cell mediated memory responses. A multivalent COVID-19 vaccine may address deficiencies in existing mRNA-based vaccines, such as the existing reliance on multiple doses and the lack of infection [1]. Multivalent vaccines rely on incorporating SARS-CoV-2 S epitopes from multiple variants, rather than just a single variant.…”
Section: Vaccination Fatiguementioning
confidence: 99%
“…For COVID-19, this is neutralizing antibodies at mucosal sites in the nose, throat, and upper respiratory tract achieved by intranasal (IN) vaccines [13]. Early data indicate that a heterologous vaccination with an mRNA intramuscular (IM) vaccine prime coupled with an IN boost could result in broader protection, both systemically and at the infection site [1,14].…”
Section: Vaccination Fatiguementioning
confidence: 99%
See 1 more Smart Citation